2015
DOI: 10.1039/c4sm02492c
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of jammed colloidal shells onto micron-sized bubbles by ultrasound

Abstract: Stabilization of gas bubbles in water by applying solid particles is a promising technique to ensure long-term stability of the dispersion against coarsening. However, the production of large quantities of particle stabilized bubbles is challenging. The delivery of particles to the interface must occur rapidly compared to the typical time scale of coarsening during production. Furthermore, the production route must be able to overcome the energy barriers for interfacial adsorption of particles. Here we demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…We also observed that initially spherical emulsion droplets attain pronounced non-spherical shapes (Fig. 6b), a property which is known for bubbles 15 and emulsion droplets 36 stabilized by hard particles. Thus, core-shell particles at the oil-water interface seem to Fig.…”
Section: Stabilization Of Bubbles and Emulsion Droplets By Core-shellsupporting
confidence: 64%
See 3 more Smart Citations
“…We also observed that initially spherical emulsion droplets attain pronounced non-spherical shapes (Fig. 6b), a property which is known for bubbles 15 and emulsion droplets 36 stabilized by hard particles. Thus, core-shell particles at the oil-water interface seem to Fig.…”
Section: Stabilization Of Bubbles and Emulsion Droplets By Core-shellsupporting
confidence: 64%
“…We would like to note that electrolyte addition, a well-known way to promote interfacial adsorption of particles, 15 did not seem to help interfacial adsorption of hard particles. We ascertained that for electrolyte concentrations up to 500 mM sodium chloride the very long timescales for surface pressure development by hard particles remain unchanged (data not shown).…”
Section: Interfacial Tensiometrymentioning
confidence: 94%
See 2 more Smart Citations
“…Soft stacking system which is composed by cells [1], particles [2] as well as other soft units [3][4][5] often presents particular arrangement. Comparing the soft stacking system with the atom stacking system in solid state physics, the former has more complex structures.…”
Section: Introductionmentioning
confidence: 99%